2003
DOI: 10.1007/s00253-003-1282-y
|View full text |Cite
|
Sign up to set email alerts
|

Removal of inorganic and organic mercurials by immobilized bacteria having mer-ppk fusion plasmids

Abstract: Feasibility of biological mercury removal from wastewater was examined by using alginate-immobilized cells of Escherichia coli carrying mer-ppk fusion plasmid pMKB18. Immobilized cells engineered to express mercury-transport system, organomercurial lyase and polyphosphate efficiently removed organic and inorganic mercury from contaminated wastewater over a wide concentration range of mercurials, probably via intracellular accumulation mediated by ppk-specified polyphosphate. Bioaccumulation of mercury was sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…[9][10][11] In theory, plants engineering expression of polyP would also reduce mercury toxicity and accumulate more mercury from the polluted sites. As expected, we found that tobacco plant genetically engineered to express bacterial polyP was more resistant to Hg 2ϩ than its wild-type progenitors.…”
mentioning
confidence: 99%
“…[9][10][11] In theory, plants engineering expression of polyP would also reduce mercury toxicity and accumulate more mercury from the polluted sites. As expected, we found that tobacco plant genetically engineered to express bacterial polyP was more resistant to Hg 2ϩ than its wild-type progenitors.…”
mentioning
confidence: 99%
“…We have previously shown that polyphosphate, a biomolecule is capable of reducing the cytotoxicity of the transported Hg(II) and retaining more mercury in the living cells but without the cells via chelation formation with polyphosphate. [27][28][29] In conclusion, this study showed for the first time that in addition to MerE and MerT, MerF and MerC are broadspectrum mercury transporters that mediate the transport of mercuric ions and phenylmercury. Thus, in addition, MerC is the most efficient tool for designing a potential bioreactor used in environmental bioaccumulation of mercurial pollution.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] The additional mer gene, merG, located between merA and merB1 on pMRA17, is 654 bp long, encoding a 217-amino acid polypeptide. 29) The predicted amino acid sequence of the gene product (MerG) has a good leader sequence that contains a short, positively charged region at N-terminus, followed by a hydrophobic region and a signal peptide cleavage site (alanine-leucine-alanine-alanine, ALAA) at position [32][33][34][35]. This characteristic N-terminal sequence is homologous to the "leader sequences" of known periplasmic proteins.…”
Section: Function Of Pseudomonas K-62 Mer Genesmentioning
confidence: 99%
“…The immobilized cells engineered to express the mercury transport system, organomercurial lyase, and polyphosphate efficiently removed both organic and inorganic mercury from contaminated wastewater over a wide concentration range of mercurials, probably via intracellular accumulation mediated by ppk-specified polyphosphate. 35) Almost all of the mercurials that disappeared in the wastewater had accumulated in the alginate beads. The Hg 2+ and C 6 H 5 Hg + coexisting in the medium were also simultaneously and efficiently removed by the immobilized cells carrying pMKB18.…”
Section: Genetically Engineered Bacteria For Mercury Remediationmentioning
confidence: 99%
See 1 more Smart Citation